2011
DOI: 10.1186/1757-7241-19-14
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide intoxication as part of smoke inhalation - a review on diagnosis and treatment from the emergency perspective

Abstract: This paper reviews the current literature on smoke inhalation injuries with special attention to the effects of hydrogen cyanide. It is assumed that cyanide poisoning is still an overlooked diagnosis in fire victims. Treatment against cyanide poisoning in the emergency setting should be given based on the clinical diagnosis only. Oxygen in combination with a recommended antidote should be given immediately, the first to reduce cellular hypoxia and the second to eliminate cyanide. A specific antidote is hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 46 publications
0
65
0
1
Order By: Relevance
“…Many patients are at increased risk of multiple potential causes such as thiamine deficiency or liver dysfunction in septic shock 18 , seizures in the setting of alcohol intoxication or drug abuse 147,148 or cyanide/carbon monoxide poisoning in the setting of burns with concurrent smoke inhalation 149 .…”
Section: Approach To the Patient With Elevated Lactatementioning
confidence: 99%
“…Many patients are at increased risk of multiple potential causes such as thiamine deficiency or liver dysfunction in septic shock 18 , seizures in the setting of alcohol intoxication or drug abuse 147,148 or cyanide/carbon monoxide poisoning in the setting of burns with concurrent smoke inhalation 149 .…”
Section: Approach To the Patient With Elevated Lactatementioning
confidence: 99%
“…However, mild CO poisoning is recognized as a cause of permanent neurological injury, ranging from extrapyramidal manifestations of varying intensity to a persistent vegetative state progressing over the years. ( 40 ) …”
Section: Hcn Poisoningmentioning
confidence: 99%
“…The physiological rationale is based on a greater induction of nitric oxide formation in the bloodstream, nitric oxide competing with HCN for the binding to the enzyme cytochrome c oxidase a. ( 40 ) A quasi-experimental study showed no reduction in blood concentrations of HCN after HBOT in SII victims. ( 43 ) …”
Section: Hcn Poisoningmentioning
confidence: 99%
“…Carbon monoxide (CO) and hydrogen cyanide (HCN) are two of the main noxious gases [1,2], whereby HCN is formed by an incomplete combustion of materials containing nitrogen [3]. These materials may be natural materials, such as wool, silk and feathers or synthetic plastics, such as polyacrylonitrile (PAN), polyamide and polyurethane.…”
Section: Introductionmentioning
confidence: 99%